Strategy for Allocating Financial Resources in Public Financial Management - Murodov Shavkatjon Farkhodovich (International Journal on Integrated Education, 2022)
Purpose: The main purpose of the study is to identify the role and significance of the distribution of financial resources in modern conditions and substantiate the main directions of the formation of financial resources in public finance management. Method: An institutional methodology was used using the methods of logical analysis, comparative evaluation of statistical data, abstraction, analysis of the best practices of foreign countries. Results: The results of the study are of both theoretical and practical interest and can be recommended to regional organizations of the Ministry of Innovative Development and the Ministry of Finance of the Republic of Uzbekistan for use in determining priority areas for venture investment.